Promoting water-related innovation through networked acceleration: Insights from the Water Innovation Accelerator. (10th January 2018) - Gabrielsson, Jonas; Politis, Diamanto; Persson, Kenneth M.; Kronholm, Johan
Abstract: The current state of the water and sanitation sector has put water-related innovations high on the global policy agenda. However, the systemic complexity that typically surrounds such contexts call for actionable knowledge of how to enable and orchestrate innovative solutions by connecting different players via organized networks. In this study we explore and analyse the Water Innovation Accelerator, which is a virtual network-centred incubator model designed and implemented in Sweden. Framed by theory and research on open innovation, incubation models, and entrepreneurial networks we provide an analysis of the design, working and performance of the Water Innovation Accelerator. In sum, our findings provide empirical support for virtual accelerators as an effective means to aid the development and market uptake of water related innovative solutions. Its overall effectiveness builds on its ability to bring private and public actors with different assets and competencies together via its entrepreneurial network, where the incubator team play a critical role for identifying and encouraging network-embedded innovation opportunities. However, the perceived effectiveness of the acceleration process for SMEs seems to be contingent on whether they are positioned in later stages of the innovation process, as well as their proximity to the incubator network. In these respects, the study provides valuable insights that may aid researchers, incubation managers and policy makers in current and future efforts to accelerate water innovation. Highlights: Virtual incubators can effectively support the development of water innovation. Cooperation and knowledge exchange are created via the entrepreneurial network. The incubator team play a critical role for identifying network opportunities. Stage of innovation and proximity to incubator network influence perceived value.